Cardiometabolic Modification of Amyloid Beta in Alzheimer’s Disease Pathology - Hefner, Marleigh; Baliga, Vineet; Amphay, Kailinn; Ramos, Daniela; Hegde, Vijay (Frontiers in Aging Neuroscience, 2021)
In recent years, several studies have suggested that cardiometabolic disorders, such as diabetes, obesity, hypertension, and dyslipidemia, share strong connections with the onset of neurodegenerative disorders such as Parkinson’s and Alzheimer’s Disease (AD). However, establishing a definitive link between medical disorders with coincident pathophysiologies is difficult due to etiological heterogeneity and underlying comorbidities. For this reason, amyloid beta (Aβ), a physiological peptide derived from the sequential proteolysis of amyloid precursor protein (APP), serves as a crucial link that bridges the gap between cardiometabolic and neurodegenerative disorders. Aβ normally regulates neuronal synaptic function and repair; however, the intracellular accumulation of Aβ within the brain has been observed to play a critical role in AD pathology. A portion of Aβ is believed to originate from the brain itself and can readily cross the blood-brain barrier, while the rest resides in peripheral tissues that express APP required for Aβ generation such as the liver, pancreas, kidney, spleen, skin, and lungs. Consequently, numerous organs contribute to the body pool of total circulating Aβ, which can accumulate in the brain and facilitate neurodegeneration. Although the accumulation of Aβ corresponds with the onset of neurodegenerative disorders, the direct function of periphery born Aβ in AD pathophysiology is currently unknown. This review will highlight the contributions of individual cardiometabolic diseases including cardiovascular disease (CVD), type 2 diabetes (T2D), obesity, and non-alcoholic fatty liver disease (NAFLD) in elevating concentrations of circulating Aβ within the brain, as well as discuss the comorbid association of Aβ with AD pathology.